The fierce tribe : masculine identity and performance in the Circuit - Weems, Mickey (UPCC book collections on Project MUSE., 2008)
"In this ethnography that documents the folk nature of popular culture, Mickey Weems applies interdisciplinary interpretation to a subject that demands such a breakdown of intellectual boundaries. The Circuit, an expression of gay culture, comprises large dance events--gatherings, celebrations, communions, festivals. Music and dance drive complex, shared performances--electronic house music played by professional DJs and mass ecstatic dancing that engenders communitas. Other performances, from drag queens and concerts to contests, theatrics, and the individual display of muscular bodies are part of the festivities. Body sculpting through muscle building is strongly associated with the Circuit, and masculine aggression is both displayed and parodied. Weems, a participant-observer with a multidisciplinary background in anthropology, folklore, religious studies, cultural studies, and somatic studies, considers the cultural and ethical dimensions of what to outsiders might seem to be just wild, flamboyant parties. He compares the Circuit to other traditions of ecstatic and communal dance, and uses his grounding in African-Brazilian Candomblé and in religious studies to illuminate spiritual experiences reported by Circuit participants. And, as a U.S. Marine, he offers the nonviolent masculine arrogance of Circuiteers as an alternative to the violent forms of masculine aggression embedded in the military and much of western culture."--Publisher's description.